THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND SELF-EFFICACY TO ENTREPRENEURIAL INTENTION - Lamanepa, Amelia Wulandari; Sidharta, Helena (International Business Management - Universitas Ciputra, 2019)
One way of overcoming unemployment and improving Indonesian economy is by increasing the number of entrepreneurs. The intention to be an entrepreneur must be created among the young generation. This study aims to determine the effect of entrepreneurship education and selfefficacy to entrepreneurship intention especially on high school students who will finish the school (case study at C School in Surabaya). The sample consists of 44 respondents. The result shows that self-efficacy has significant effects on entrepreneurship intention, but entrepreneurship education does not significantly affect entrepreneurship intention.